An Introduction to Cenozoic Macrofossils of Indonesia - J.T. (Han) van Gorsel (Ikatan Ahli Geologi Indonesia, 2014)
A brief overview is presented of the principal groups of Cenozoic macrofossils from outcrops in Indonesia. Prior to the 1930's macrofossils, in particular mollusks, were the principal objects of paleontological and biostratigraphic studies in Indonesia. Since then focus has shifted to microfossils, but it is argued that macrofossils still have the potential to significantly contribute to the knowledge of biostratigraphy, paleoenvironments, paleoclimate, paleobiogeography and plate tectonic reconstructions of the region. Cenozoic marine macrofossil assemblages from Indonesia all represent tropical faunas of Indo-Pacific province affinity.